Effects of exercise on BDNF-TrkB signaling in the paraventricular nucleus and rostral ventrolateral medulla in rats post myocardial infarction. (August 2020) - Lee, Heow Won; Ahmad, Monir; Wang, Hong-Wei; Leenen, Frans H.H.
Abstract: Brain-derived neurotrophic factor (BDNF)-tropomyosin-related kinase B (TrkB) signaling in the paraventricular nucleus (PVN) and rostral ventrolateral medulla (RVLM) is associated with cardiovascular regulation. Exercise increases plasma BDNF and attenuates activation of central pathways in the PVN and RVLM post myocardial infarction (MI). The present study assessed whether MI alters BDNF-TrkB signaling and intracellular factors Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) and Akt in the PVN and RVLM of male Wistar rats with or without exercise or treatment with the TrkB blocker ANA-12. A 4-week period of treadmill exercise training was performed in MI rats. A separate experiment was conducted with 2.5 mg/kg ANA-12 in sedentary MI rats. At 5 weeks post MI, in both the PVN and RVLM, the ratio of full-length TrkB (TrkB.FL) and truncated TrkB (TrkB.T1) was decreased. 0.5 mg/kg ANA-12 did not affect BDNF-TrkB signaling and cardiac function post MI, but 2.5 mg/kg ANA-12 further decreased ejection fraction (EF). Exercise increased mature BDNF (mBDNF) and decreased Akt activity in the PVN, whereas in the RVLM, exercise did not affect mBDNF but lowered p-CaMKIIβ. ANA-12 prevented the exercise-induced increase in mBDNF in the PVN and decrease in p-CaMKIIβ in the RVLM. In conclusion, exercise decreases Akt activity in the PVN and decreases p-CaMKIIβ in the RVLM post MI. BDNF-TrkB signaling only mediates the decrease in p-CaMKIIβ in the RVLM. The exercise-induced decreases in Akt activity in the PVN and p-CaMKIIβ in the RVLM may contribute to the attenuation of the decrease in EF and sympathetic hyperactivity post MI.